NUZAL MEDIEVAL BURIAL (ALAGIR GORGE, NORTH OSSETIA): RESULTS OF CRANIOLOGICAL RESEARCH - Frizen, Sergej Ur'evic; Krutogolovenko, Konstantin Aleksandrovic; Sal'nikova, Anna Dmitrievna (History, Archeology and Ethnography of the Caucasus, 2023)
The article discusses the results of the study of craniological materials from the Nuzalsky medieval soil burial ground located in the Alagir Gorge of the Republic of North Ossetia-Alania and fully excavated in 2020. 213 individuals were studied, the craniological series included 18 male and 9 female skulls, the individual data of which are given in the tables. The series cannot be called homogeneous, but it is not possible to single out any definite morphological variants in it. For intergroup comparison, the following were used: series from the burial grounds of the early and medieval Alanian culture, the medieval population from the crypts of the mountainous Ingushetia and the crypts of Tsoi-Pede, and the combined series of Irons, Digors and Tuals. Based on the results of the intergroup comparison, a conclusion is made about the formation of the studied population on the basis of the Alanian and mountainous components. We also collected materials for the study of paleoDNA. In the future, the results of the study are expected to be compared with the results of whole genome sequencing of samples from a number of sites, which will allow DNA methods to assess the ratio of the contribution of the mountain and Alan populations to the gene pool of the Nuzala population.
Keywords: Caucasus; North Ossetia-Alania; Middle Ages; archeology; paleoanthropology; craniology; paleoDNA; whole genome sequencing